Ascorbate Inhibits Proliferation and Promotes Myeloid Differentiation in TP53-Mutant Leukemia - Smith-Díaz, Carlos C.; Magon, Nicholas J.; McKenzie, Judith L.; Hampton, Mark B.; Vissers, Margreet C. M.; Das, Andrew B. (Frontiers in Oncology, 2021)
Loss-of-function mutations in the DNA demethylase TET2 are associated with the dysregulation of hematopoietic stem cell differentiation and arise in approximately 10% of de novo acute myeloid leukemia (AML). TET2 mutations coexist with other mutations in AML, including TP53 mutations, which can indicate a particularly poor prognosis. Ascorbate can function as an epigenetic therapeutic in pathological contexts involving heterozygous TET2 mutations by restoring TET2 activity. How this response is affected when myeloid leukemia cells harbor mutations in both TET2 and TP53 is unknown. Therefore, we examined the effects of ascorbate on the SKM-1 AML cell line that has mutated TET2 and TP53. Sustained treatment with ascorbate inhibited proliferation and promoted the differentiation of these cells. Furthermore, ascorbate treatment significantly increased 5-hydroxymethylcytosine, suggesting increased TET activity as the likely mechanism. We also investigated whether ascorbate affected the cytotoxicity of Prima-1Met, a drug that reactivates some p53 mutants and is currently in clinical trials for AML. We found that the addition of ascorbate had a minimal effect on Prima-1Met–induced cytotoxicity, with small increases or decreases in cytotoxicity being observed depending on the timing of treatment. Collectively, these data suggest that ascorbate could exert a beneficial anti-proliferative effect on AML cells harboring both TET2 and TP53 mutations whilst not interfering with targeted cytotoxic therapies such as Prima-1Met.